Avaliação dos efeitos metabólico e oxidativo em cirurgia cardíaca pediátrica : influência da técnica anestésica - Dumaresq, Danielle Maia Holanda (2006)
Pediatric cardiac surgery often requires cardiopulmonary bypass (CPB) during the surgical intervention. CPB and surgical stress combination evokes a multifatorial systemic inflammatory response with activation of the humoral and cellular cascade. In addition, CPB provides ischemia-reperfusion periods, leading to favorable conditions to free radical production and creating an imbalance, knew as oxidative stress. Reactive Oxygen Species (ROS) formed during the ischemia-reperfusion period are strongly implicated in the pathogenesis of the transitory myocardial dysfunction (stunning heart), myocardial necrosis, programmed cell death (apoptosis), vascular dysfunction and postischemic dysrhythmias. The anesthetic technique influence on the metabolic and oxidative response was evaluated in 20 children with congenital heart disease, randomized in two groups: GP, group which used venous total anesthesia with propofol, and GS, the group which used balanced anesthesia with sevoflurano. Thiobarbituric acid-reactive substance (TBARS), glutatione, lactate and pyruvate plasmatic concentrations were determined in three times: T0, after radial artery canulation, T1, 30 minutes after CPB start and T2, at the end of procedure. The markers evaluation in the several times and in each group, the Friedman test was used. The Wilcoxon test was used to compare the medians between the groups. Pearson correlation was done to evaluate the markers between the groups. Values of p<0.05 were considered statistically significant. The TBARS, gluthatione, lactate and pyruvate concentrations did not change significantly in the observed times (p>0,05, Friedman test). When the marker’s median values was compared between the groups, it wasn’t significant (p>0,05, Wilcoxon test). The quotient of the relationship between lactate and pyruvate (L/P) was greater than 10 in both groups, with no difference statistically significant. There was a moderate Pearson correlation for TBARS, in T1 (r=0,50; p=0,13) e T2(r=0,51;p=0,12). During the CPB (T1), there was a high Pearson correlation between the groups for lactate (r=0,68; p=0,02), piruvato (r=0,75; p=0,01) e L/P rate (r=0,83; p=0,003). The comparison of two anesthetic techniques with distinct action mechanisms, allow confronting inhalator and venous anesthetic protecting proprieties. The anesthetic techniques investigated in this study were similar, without metabolic and oxidative stress substrates augment, in congenital heart disease surgical correction of acianotic children